Thermal Shock Resistance of Chemical Vapour Deposited Zinc Sulfide at Elevated Temperatures. Issue 4 (1st October 2016) - Cheng, Tianbao; Li, Weiguo; Qu, Zhaoliang; Wen, Weibin; Fang, Daining
Abstract: For traditional bulk ceramics, the compressive strength is much greater than the tensile strength. Thus, only the tensile failure is usually considered in the thermal shock resistance (TSR) of these ceramics. However, the compressive strength of chemical vapour deposited (CVD) zinc sulfide (ZnS) is relatively low. It thus becomes critical in evaluating the TSR of CVD ZnS at elevated temperatures. In the present work, the compressive and tensile strengths are measured from room temperature to 600°C and then the TSR of CVD ZnS is studied. It is found that the TSR of CVD ZnS under aerodynamic thermal environments will be over-estimated significantly if the compressive strength is neglected. The study also shows the importance of considering the temperature dependence of the material properties to evaluate the TSR of CVD ZnS. Moreover, convective cooling can improve the TSR of CVD ZnS caused by aerodynamic heating at the upper surface. However, it can also lead to thermal down shock at the lower surface. To ensure that convective cooling will not cause the fracture of CVD ZnS, heat transfer condition should be less than the corresponding critical heat transfer condition. GRAPHICAL ABSTRACT: